ETIKA BERBEDA PENDAPAT DALAM PERSPEKTIF MODERASI BERAGAMA - Farina, Dahlia; Musdalifa, Deby Habja; Julhadi, Julhadi; Wahyuni, Sri (Ensiklopedia of Journal, 2026)
Differences of opinion are an inherent part of Islamic intellectual tradition and become a social reality in the religious life of Indonesian Muslims. However, the emergence of digital media, shifting patterns of authority, and the increasing politicization of religious symbols often exacerbate tensions within communities. This article examines how disagreements can be managed ethically through the framework of religious moderation. Using a qualitative library research method, the study reviews classical Islamic discourses on ikhtilaf, national policy documents on religious moderation, and contemporary socio-religious dynamics in Indonesia. The findings show that conflicts rarely arise from the substance of theological or jurisprudential differences, but rather from communication patterns, emotional responses, and weak religious literacy. The principles of moderation such as balance, tolerance, anti-violence, and respect for local traditions provide a constructive approach for interacting across divergent viewpoints. The study concludes that courteous disagreement is not only an ethical imperative but also a civic necessity for sustaining social harmony in a pluralistic nation.Keywords: Disagreement, Religious Moderation, Islamic Ethics, Tolerance